Implementation of ERP and SCM System to Improve Productivity and Competitive Advantage of Veneer Sales at PT Karya Megah Indowood - Bayu Setyo Nugroho; Dody Setyadi; Sri Marhaeni Salsiyah; Alyssa Chaerunnisa; Della Amelia; Rifqi Irwandika; Aliya Shafina Augusta Sudjarwo (Indonesian Journal of Information Systems, 2025)
PT Karya Megah Indowood is a company engaged in veneer manufacturing. The company does not utilize renewable technology to create a system that can assist the company in managing its operations. By not using adequate technology, the company takes more time for its administrative activities, thus affecting the company's productivity. The lack of technology and integrated management systems also leads to a lack of efficiency in inventory management, distribution, and internal communication, hindering the company's growth. It is expected that an integrated technology system can assist the company in increasing its productivity. The problems faced by the company can be improved through the implementation of technology in the Supply Chain Management process and Enterprise Resource Planning using the odoo system. The use of Purchase, Inventory, Sales, and CRM modules is an application in odoo that is applied to purchase goods, check inventory, and strengthen the company's relationship with customers at PT Karya Megah Indowood so that the company's productivity will increase.